Analysis of the Decision of Micro and Small Entrepreneurs to Become Customers of Sharia Financial Institutions - Hidayat, Farid (Profesional Muda Cendekia Publishing, 2024)
ABSTRACT Research Aims: This study aims to analyze the influence of religiosity, Sharia compliance, pricing, promotion, and process, on the decision of micro and small rulers to become customers of the Islamic finance industry. Design/methodology/approach: This study uses a quantitative method, the number of samples in this study is 137 respondents. The sampling method uses Purposive sampling, with the criteria of 1. Micro and Small Entrepreneurs in Temanggung Regency; 2. As a customer of the Islamic finance industry. Data analysis was carried out using the Partial Least Square (PLS) method using smart-pls 3. Research Findings: religiosity and process variables have a significant positive effect on the decision of micro and small rulers to become customers of the Islamic financial industry, while sharia compliance, price, and promotion do not affect the decision of micro and small rulers to become customers of the Islamic financial industry. Theoretical Contribution/Originality: A person's religiosity is embedded in a person, a person's religiosity affects what a person does. The transaction process in the financial industry is very important to pay attention to and can be an element in the field of marketing that influences someone to become a customer. Keywords: religiosity, sharia compliance, price, process and promotion